Understanding the effect of Li and flow velocity on corrosion deposition at 230 °C hydrogenated water. (15th May 2020) - Cassineri, Stefano; Cioncolini, Andrea; Curioni, Michele; Morrison, Jonathan; Banks, Andrew; Stevens, Nicholas; Scenini, Fabio
Highlights: CRUD build-up increased following a power law with the fluid velocity. Electrokinetic deposition induced CRUD deposition occurred at alkaline pH (2–2.5 ppm of Li). Magnetite solubility and build-up rate decreased at alkaline pH. Particulate oxide build-up was negligible at high pH. Abstract: The effect of flow velocity, pH and lithium concentration on corrosion product deposition in accelerated flow regions was investigated in simulated nuclear reactor primary water using discs containing micro-orifices. The results also showed that a well adhered crystalline deposit formed between 2 and 2.5 ppm lithium, where the zeta potential of stainless-steel specimens is negative and the electrokinetic effects are expected to dominate. Conversely, a loosely adherent deposit driven by the deposition of particulates was formed for lower lithium concentrations.